Does telephone-delivered exercise advice and support by physiotherapists improve pain and/or function in people with knee osteoarthritis? Telecare randomised controlled trial. Issue 13 (20th November 2019) - Hinman, Rana S; Campbell, Penny K; Lawford, Belinda J; Briggs, Andrew M; Gale, Janette; Bills, Caroline; Kasza, Jessica; Harris, Anthony; French, Simon D; Bunker, Stephen J; Forbes, Andrew; Bennell, Kim L
Abstract : Objective: Evaluate a physiotherapist-led telephone-delivered exercise advice and support intervention for people with knee osteoarthritis. Methods: Participant-blinded, assessor-blinded randomised controlled trial. 175 people were randomly allocated to (1) existing telephone service (≥1 nurse consultation for self-management advice) or (2) exercise advice and support (5–10 consultations with a physiotherapist trained in behaviour change for a personalised strengthening and physical activity programme) plus the existing service. Primary outcomes were overall knee pain (Numerical Rating Scale, range 0–10) and physical function (Western Ontario and McMaster Universities Osteoarthritis Index, range 0–68) at 6 months. Secondary outcomes, cost-effectiveness and 12-month follow-up were included. Results: 165 (94%) and 158 (90%) participants were retained at 6 and 12 months, respectively. At 6 months, exercise advice and support resulted in greater improvement in function (mean difference 4.7 (95% CI 1.0 to 8.4)), but not overall pain (0.7, 0.0 to 1.4). Eight of 14 secondary outcomes favoured exercise advice and support at 6 months, including pain on daily activities, walking pain, pain self-efficacy, global improvements across multiple domains (overall improvement, improved pain, improved function and improved physical activity) and satisfaction. By 12 months, most outcomes were similar between groups. Exercise advice and support cost A514/participant and did not save other health service resources. Conclusion: Telephone-delivered physiotherapist-led exercise advice and support modestly improved physical function but not the co-primary outcome of knee pain at 6 months. Functional benefits were not sustained at 12 months. The clinical significance of this effect is uncertain. Trial registration number: Australian New Zealand Clinical Trials Registry (#12616000054415).